2001
DOI: 10.1046/j.1365-2249.2001.01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces expression of the chemokines monocyte chemoattractant protein-1 (MCP-1) and IL-8 in human dermal fibroblasts

Abstract: SUMMARYHypoxia is an important factor in the pathophysiology of vascular and inflammatory diseases. Leucocyte infiltration, as a consequence of adhesion molecule up-regulation and chemokine release, is a prominent feature of these diseases. The objective of our study was to investigate the potential role of resident fibroblasts in hypoxia-induced chemotactic responses. We show that MCP-1 and IL-8 mRNA are specifically induced by hypoxia in dermal fibroblasts. This response is paralleled by increased NF-kB p65/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 37 publications
3
61
3
Order By: Relevance
“…Increased MCP-1 mRNA and protein expression was reported in human dermal fibroblasts exposed to hypoxia (44), and human melanoma cell lines were shown to up-regulate MCP-1 mRNA and protein under anoxia/reoxygenation (45). Moreover, stimulatory effects of hypoxia on MCP-1 have been observed in ischemic rat neurons and myocardial cells (46,47).…”
Section: Discussionmentioning
confidence: 98%
“…Increased MCP-1 mRNA and protein expression was reported in human dermal fibroblasts exposed to hypoxia (44), and human melanoma cell lines were shown to up-regulate MCP-1 mRNA and protein under anoxia/reoxygenation (45). Moreover, stimulatory effects of hypoxia on MCP-1 have been observed in ischemic rat neurons and myocardial cells (46,47).…”
Section: Discussionmentioning
confidence: 98%
“…16,25 --27 On the other hand, it is also reported that hypoxia could induce MCP-1 expression in human dermal fibroblasts and hypoxic brain. 28,29 However, the mechanism behind the downregulation of MCP-1 mRNA is not clear, but the group of Safronova et al 30 suggested a histone deacetylases dependent one. They report that hypoxia induces the deacetylation of histones and therefore repression of MCP-1 mRNA transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been reported to upregulate MCP-1 expression in human dermal fibroblasts, 40 neonatal rat brain 41 and melanona cells. 42 The formation of MCP-1 is reduced by hypoxia in ovarian cancer cells, 43 macrophages 44,45 and human synovial fibroblasts.…”
Section: Discussionmentioning
confidence: 99%